Vocabulary Learning and Retention Using Semantic Mapping Technique At 7th Grade Of SMPN 2 Sakra Timur. - Istiqomah; Boniesta Zulandha Melani; Agus Saputra (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2025)
Abstract: Vocabulary plays a crucial role in English language acquisition, serving as the foundation for developing listening, speaking, reading, and writing skills. This study investigates the effectiveness of the semantic mapping technique in improving vocabulary learning and retention among seventh-grade students at SMPN 2 Sakra Timur. This study employs a pre-experimental design, The study involves a single experimental group of 30 students who underwent pre-test, post-test, and delayed post-test assessments. Data were analyzed using Repeated Measures ANCOVA to find out significant differences across testing phases. The results indicate that the semantic mapping technique significantly improved students' vocabulary learning, as evidenced by a substantial increase in post-test scores compared to pre-test scores (p = 0.007, n = 0.235). However, the technique did not significantly improve students' retention, as evidenced by the non-significant interaction between time and pre-test scores (p = 0,137, n = 0.077). These findings suggest that while semantic mapping is effective in facilitating initial vocabulary learning, its impact on long-term retention remains limited.